The Parameters Optimizing Design of Double Suspension Arm Torsion Bar in the Electric Sight-Seeing Car by Random Vibration Analyzing Method - Shui-Ting Zhou; Yi-Jui Chiu; I-Hsiang Lin (Shock and Vibration)
This study is about the impact of the performance and the sensitivity analysis for parameters of the torsion bar suspension in the electric sight-seeing car, which the authors’ laboratory designed and which is used in the authors’ university. The suspension stiffness was calculated by using the virtual work principle, the vector algebra, and tensor of finite rotation methods and was verified by the ADAMS software. Based on the random vibration analysis method, the paper analyzed the dynamic tire load (DTL), suspension working space (SWS), and comfort performance parameters. For the purpose of decreasing the displacement of the suspension and limiting the frequency of impacting the stop block, the paper examined the three parameters and optimized the basic parameters of the torsion bar. The results show that the method achieves a great effect and contributes an accurate value for the general layout design.